2015
DOI: 10.1016/j.bbamcr.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

GSKIP- and GSK3-mediated anchoring strengthens cAMP/PKA/Drp1 axis signaling in the regulation of mitochondrial elongation

Abstract: GSK3β binding of GSKIP affects neurite outgrowth, but the physiological significance of PKA binding to GSKIP remains to be determined. We hypothesized that GSKIP and GSK3β mediate cAMP/PKA/Drp1 axis signaling and modulate mitochondrial morphology by forming a working complex comprising PKA/GSKIP/GSK3β/Drp1. We demonstrated that GSKIP wild-type overexpression increased phosphorylation of Drp1 S637 by 7-8-fold compared to PKA kinase-inactive mutants (V41/L45) and a GSK3β binding-defective mutant (L130) under H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…23 Similar results have also been observed in non-transformed cells, including MEF and HEK293 cells. 6,24 Consistent with these observations, we have shown that activation of PKA induced by energy stress clearly promotes DRP1 phosphorylation at Ser637 and subsequent mitochondrial elongation in HCC cells. However, we still cannot rule out the possibility that other kinases may be involved in this process.…”
Section: Discussionsupporting
confidence: 78%
“…23 Similar results have also been observed in non-transformed cells, including MEF and HEK293 cells. 6,24 Consistent with these observations, we have shown that activation of PKA induced by energy stress clearly promotes DRP1 phosphorylation at Ser637 and subsequent mitochondrial elongation in HCC cells. However, we still cannot rule out the possibility that other kinases may be involved in this process.…”
Section: Discussionsupporting
confidence: 78%
“…However, Ser637 phosphorylation reverses this process. 5 Drp1 is phosphorylated by specific kinases and signaling pathways during mitochondrial fission, including phosphoglycerate mutase family member 5, 6 AMPK, [7][8][9] MAPK, [10][11][12] , and cyclin-dependent kinase 1/cyclin B1 (Cdk1/cyclin B1). 13 AMPK is not only an important detector of energy levels but is also a negative moderator of glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main proteins implicated in mitochondrial fission is the GTPase dynamin-1-like protein (DRP1) that can be activated through phosphorylation by ERK at Serine 616 in mouse and human cells 37 , 38 . Conversely, phosphorylation of DRP1 at Serine 637 by PKA inactivates the protein leading to mitochondrial fusion 39 41 . Of interest, TGR5 stimulation in Tgr5 +/+ adipocytes increased DRP1 phosphorylation specifically at Serine 616, but not at Serine 637 (Fig.…”
Section: Resultsmentioning
confidence: 99%